Fertility levels and differentials in Malaysia / Lim Evone - Lim , Evone (2020)
The main objective of this paper is to examine the fertility differentials among women by selected socio-economic and demographic variables in Malaysia. Over the past 40 years, the fertility level in Malaysia has declined considerably due to social and economic changes and has been below the replacement level of 2.1 children since 2013. The problem of population aging in Malaysia rises due to the increasing people’s life expectancy and declining fertility rates. It is critical for Malaysian policymakers to have a deeper understanding of the factors influencing fertility behavior. The fifth series of the Malaysian Population and Family Survey (MPFS-5) collected in 2014 is used as the main data source. Bivariate analysis is conducted on a sample of 5,146 women to determine how fertility varies with selected socio-economic and demographic factors such as women’s age, stratum, state, ethnicity, the highest education level of women, age at first marriage, the current employment status of women and the status of family planning. Moreover, this paper examines the significant relationship between these variables and the difference in the number of children ever born by women. This study found that all of the selected factors have a significant effect on fertility differentials in Malaysia. In brief, fertility patterns are different across socio-demographic subgroups and over time.